+0

Systems of Equations

+1
41
1

x = 2y -5

5x -6y = 7

Guest Oct 24, 2017

#1
+5261
+1

x  =  2y - 5

5x - 6y  =  7        Since  x = 2y - 5 , we can substitute  2y - 5  in for  x .

5(2y - 5) - 6y  =  7           Distribute  5  to the terms in partenthesees.

10y - 25 - 6y  =  7            Add  25  to both sides of the equation.

10y - 6y  =  7 + 25           Combine like terms.

4y  =  32        Divide both sides by  4 .

y  =  8            Plug this value for  y  into the first equation to find  x .

x  =  2(8) - 5

x  =  16 - 5

x  =  11

hectictar  Oct 24, 2017
Sort:

#1
+5261
+1

x  =  2y - 5

5x - 6y  =  7        Since  x = 2y - 5 , we can substitute  2y - 5  in for  x .

5(2y - 5) - 6y  =  7           Distribute  5  to the terms in partenthesees.

10y - 25 - 6y  =  7            Add  25  to both sides of the equation.

10y - 6y  =  7 + 25           Combine like terms.

4y  =  32        Divide both sides by  4 .

y  =  8            Plug this value for  y  into the first equation to find  x .

x  =  2(8) - 5

x  =  16 - 5

x  =  11

hectictar  Oct 24, 2017

9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details